Assessment of patients with multiple sclerosis according to tests of the Multiple Sclerosis Functional Composite - Anelise Ineu Figueiredo; Carla Roberta Nunes Polachini; Ana Lucia Cervi Prado
Abstract Introduction: The Multiple Sclerosis Functional Composite (MSFC) is a scale that evaluates the functional and cognitive aspects of patients with multiple sclerosis (MS). Objective: To compare the performance of individuals with the relapsing-remitting form of MS (RRMS) with a group of healthy subjects using the MSFC. Methods: Twenty subjects were investigated in this study, consisting of 10 patients with clinical diagnosis of RRMS and 10 controls with similar gender and age to the group with the disease. The three tests that comprise the MSFC were used for the evaluation of gait, upper limb motor function and cognition (memory and processing speed). Student's t-test was used to assess data with normal distribution and data with skewed distribution were evaluated using the Mann-Whitney test. Results: The results showed that the patients with RRMS took longer to perform the locomotion test (6.91 ± 2.35) compared to the control group (5.16 ± 1.28). The MS group (22.06 ± 5.44) also showed greater difficulty in performing a task with the dominant upper limb compared to the healthy subjects (17.79 ± 2.96). No statistically significant difference was found between the groups in the performance of cognitive tasks (p = .65). Conclusion: The use of the MSFC tests proved valuable for measuring possible motor and cognitive impairments in patients with RRMS. Thus, it is suggested that this scale is adopted in clinical practice, improving therapies for the treatment of MS patients and thereby providing them a better quality of life.